Religion in rural late-antique Iberia - López-Gómez, José Carlos; Alvar Nuño, Antón (Routledge, Taylor & Francis, 2025)
"This volume examines the dynamism and complexity of religious expressions in rural settings across Late-Antique Iberia. Chapters demonstrate that the rural world was a dynamic space which formed an integral part of the multi-directional process of religious exchange on the Iberian Peninsula in Late Antiquity, thus refuting the idea that the rural spaces, and in turn rural religious practices, were static and unchanging, anchored in tradition and resistant to any process of religious change. The chapters present a series of case studies that examine phenomena such as the multi-locality of certain religious groups that moved periodically between the city and the countryside, the strategies that local agents used to shape religious expressions in rural areas (significantly marked by the permeability between the urban and rural worlds), the creation of religious landscapes as spaces imbued with cultural meanings by religious authorities that conceive the rural world as a place of refuge and spiritual experience, or the analysis of trans-local religious networks that connected rural and urban settings, facilitating the transmission of rituals and practices between these two spheres. Finally, both the introduction and the final chapter discuss the concept of "rural religion" and its applicability to the sphere of Late Antiquity. This volume provides a much-needed resource for students and scholars of religion in Late Antique Iberia, and in the post-Roman world more broadly, as well as anyone working on rural religion in the ancient, Late Antique and Medieval worlds"--